Trends and Challenges of AI Integration in Basic Education: Insights from a Bibliometric Study - Schwarzbach, Lucas da S.; Vicari, Rosa Maria; Ribeiro, Luis Otoni M.; Barwaldt, Regina (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC), 2025)
This article reviews 43 publications (2021-2024) on Artificial Intelligence (AI) in Basic Education, using Guedes’ (2018) methodology. A global increase in interest is noted, with China and the USA leading contributions. Prominent research areas include ”Education,” ”Technology,” ”Teacher Perceptions,” and ”Ethics,” categorized into: AI perceptions, factors in teacher adoption, and professional development. While AI has the potential to personalize learning, teacher concern and uncertainty require continuous training in technical and pedagogical skills, focusing on critical thinking and curriculum integration. The study emphasizes educational leadership and suggests future research on student-centered and adaptive learning models.